Hox genes and the evolution of diverse body plans. - Akam, M. (Philosophical transactions of the Royal Society of London. Series B, Biological sciences, 1995)
Homeobox genes encode transcription factors that carry out diverse roles during development. They are widely distributed among eukaryotes, but appear to have undergone an extensive radiation in the earliest metazoa, to generate a range of homeobox subclasses now shared between diverse metazoan phyla. The Hox genes comprise one of these subfamilies, defined as much by conserved chromosomal organization and expression as by sequence characteristics. These Hox genes act as markers of position along the antero-posterior axis of the body in nematodes, arthropods, chordates, and by implication, most other triploblastic phyla. In the arthropods this role is visualized most clearly in the control of segment identity. Exactly how Hox genes control the structure of segments is not yet understood, but their differential deployment between segments provides a model for the basis of segment diversity. Within the arthropods, distantly related taxonomic groups with very different body plans (insects, crustaceans) may share the same set of Hox genes. The expression of these Hox genes provides a new character to define the homology of different body regions. Comparisons of Hox gene deployment between insects and a branchiopod crustacean suggest a novel model for the derivation of the insect body plan.